Penerapan Strategi Pembelajaran Ekspositori di Pendidikan Anak Usia Dini - Matlani (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2023)
Today the application of learning strategies is very crucial, choosing a learning strategy is a must for the continuity of the learning process. In this study the aims were to determine the application of expository learning strategies at PAUD Bina Rahimah Pamekasan regarding: 1. stages in implementing expository learning strategies, 2. Obstacles in implementing expository learning strategies. The approach used in this study is a qualitative approach. Methods of data collection by observation, interviews, and documentation. While the data analysis is descriptive qualitative. In this study it was found that the stages carried out in the application of expository learning strategies at PAUD Bina Rahimah Pamekasan: First the preparation stage, Second presentation stage, Third correlation stage, Fourth conclusion stage, Fifth application stage. The obstacles in implementing expository learning strategies namely, the weak ability of students to catch subjects, and the large number of differences in students' ability to capture subjects and the lack of interest and talent of students towards existing subjects, especially subjects which is hard to understand.